Multiculturalism Practices Associated with the Production of Batik in Lasem - Indonesia - Amirudin; Purnomo, Mulyo Hadi (International Journal of Global Community, 2018)
This article reports the research on the dynamic relations between Chinese and natives regarding cultural production in the field of batikart in Lasem – Rembang, Indonesia. The word “field” as used in this context is traced to Bourdieu (1993, 2005), who defined field as a "system of relationships" in which actors interact dynamically to produce nonmaterial cultural products (systems of ideas, value, symbolic system) and material products (art, architecture), in this case batik art. This research aims to unveil how multicultural practices take place in the process of batikart. Through the ethnographic method of batikproduction process at a batikindustrial centre known as Rumah Batik Sekar Kencana in Karangturi Village, Lasem, the researchers traced the dynamics of the native – non-native relation that took place in this process and followed it to understand how batikas a cultural product was born in Lasem. This research finds that batik can be seen as a relatively autonomous cultural production field that has its own logic, and the practice forms a delicate social fabric that leads to the achievement of certain goals. The achievement of goals involving Javanese batikmakers, Chinese owners, and Javanese religious leaders shows how multicultural practices have taken place in Lasem not only at the level of ideas but also at the level of material culture.